The affinity of antigen-binding domain on the antitumor efficacy of CAR T cells: Moderate is better - Mao, Rui; Kong, Wanqing; He, Yukai (Frontiers in Immunology, 2022)
The overall efficacy of chimeric antigen receptor modified T cells (CARTs) remain limited in solid tumors despite intensive studies that aim at targeting multiple antigens, enhancing migration, reducing tonic signaling, and improving tumor microenvironment. On the other hand, how the affinity and engaging kinetics of antigen-binding domain (ABD) affects the CART’s efficacy has not been carefully investigated. In this article, we first analyzed 38 published solid tumor CART trials and correlated the response rate to their ABD affinity. Not surprisingly, majority (25 trials) of the CARTs utilized high-affinity ABDs, but generated merely 5.7% response rate. In contrast, 35% of the patients treated with the CARTs built from moderate-affinity ABDs had clinical responses. Thus, CARTs with moderate-affinity ABDs not only have less off-target toxicity, but also are more effective. We then reviewed the effects of ABD affinity on the biology and function of CARTs, providing further evidence that moderate-affinity ABDs may be better in CART development. In the end, we propose that a fast-on/fast-off (high Kon and Koff) kinetics of CART-target engagement in solid tumor allow CARTs to generate sufficient signaling to kill tumor cells without being driven to exhaustion. We believe that studying the ABD affinity and the kinetics of CART-tumor interaction may hold a key to designing effective CARTs for solid tumors.